FRI0256 Long-term safety of tocilizumab in patients with rheumatoid arthritis following a mean treatment duration of 3.9 years. (23rd January 2014) - Genovese, M.; Sebba, A.; Rubbert-Roth, A.; Scali, J.; Alten, R.; Kremer, J.; Pitts, L.; Vernon, E.; van Vollenhoven, R.
Abstract : Background: The IL-6 receptor inhibitor tocilizumab (TCZ) has demonstrated efficacy in improving signs/symptoms, reducing joint damage and improving function in patients (pts) with rheumatoid arthritis (RA). Objectives: To evaluate the long-term safety of TCZ in adults with RA. Methods: Analyses were performed in all pts who received ≥1 TCZ dose in 1 of 5 placebo-controlled studies (OPTION, TOWARD, RADIATE, AMBITION, LITHE), a clinical pharmacology study or long-term extension studies. In addition, 6-month data were included from the phase 4 TCZ monotherapy study (ADACTA). Data were pooled and analysed from initial TCZ exposure to 2 May 2012 (cut-off). Results: 4171 pts were included. Mean (median [range]) duration was 3.9 (5.1 [0.0-6.8]) y; total observation time was 16204.8 pt-y (PY). Rates of serious adverse events (SAEs), serious infections, myocardial infarction (MI) SAEs, stroke SAEs, hepatic SAEs and gastrointestinal (GI) perforations were stable over time (Table ). The overall rate of AEs leading to withdrawal was 4.9/100PY (95% CI, 4.6-5.3). Infections, laboratory abnormalities and neoplasms were the most common AEs leading to withdrawal (0.97/100PY, 0.87/100PY and 0.77/100PY). 8 pts withdrew due to anaphylaxis; these were previously reported. 1 Overall rates/100PY (95% CI) were 14.4 (13.9-15.0) for SAEs and 0.58 (0.47-0.71) for deaths. The most common SAEs were infections, which occurred at a rate of 4.4/100PY (95% CI, 4.1-4.8); the most common serious infection was pneumonia. Overall rates/100PY (95% CI) of MI SAEs, stroke SAEs and hepatic SAEs were 0.27 (0.20-0.36), 0.32 (0.24-0.42) and 0.04 (0.02-0.09), respectively. The GI perforation rate was 0.20/100PY (95% CI, 0.14-0.29). The rate of GI perforations in pts who received or did not receive concomitant corticosteroids was 0.2/100PY (95% CI, 0.16-0.36) and 0.1/100PY (95% CI, 0.03-0.24), respectively. There were 204 confirmed malignancies, including 68 nonmelanoma skin cancer (NMSC) cases, corresponding to an overall rate/100PY (95% CI) of 1.26 (1.09-1.44) and, excluding NMSC, of 0.84 (0.70-0.99). Image/graph: Conclusions: The safety profile of TCZ in the current analysis is consistent with that in previous analyses 1, 2 ; it remained stable over a mean duration of 3.9 y with no new safety signals emerging. References: Arthritis Res Ther 2011;13:R141; Arthritis Rheum 2012;64:S700 Disclosure of Interest : M. Genovese Grant/research support from: Roche, Consultant for: Roche, A. Sebba Consultant for: Genentech, Lilly, Novartis, Merck, Speakers bureau: Genentech, Novartis, A. Rubbert-Roth Grant/research support from: Roche, Chugai, Pfizer, Consultant for: Roche, Chugai, Pfizer, UCB, MSD, Speakers bureau: Roche, UCB, MSD, J. Scali Speakers bureau: GSK, BMS, Gador, Janssen, UCB-Montpellier, Roche, R. Alten Grant/research support from: Roche, Consultant for: Roche, Speakers bureau: Roche, J. Kremer Grant/research support from: Genentech, Consultant for: Genentech, L. Pitts Employee of: Roche, E. Vernon Employee of: Roche, R. van Vollenhoven Grant/research support from: Abbott, BMS, GSK, MSD, Pfizer, Roche, UCB, Consultant for: Abbott, BMS, GSK, MSD, Pfizer, Roche, UCB